(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
Bombus terrestris L. appears to be a promising and cosmopolitan bumblebee species for pollination of greenhouse crops and its demand for large scale rearing. For effective crop pollination, colonies with optimal body sized workers are essential because generally larger bees visit more flowers per unit time. The body size is correlated with flexible development and growth in a changing environment. This study explored the effect of different photoperiodic regimes i.e., L0:D24, L8:D16, L16:D8 and L24:D0 in regulation of the body mass and size of bumblebee workers during the stages of larval, pupal and adult eclosion. The results showed that wet masses of larvae, pupae and adult ranged from 144.2 ± 7.6 to 198.7 ± 11.7, 398.3 ± 16.0 to 464.7 ± 9.3 and 224.8 ± 9.3 to 274.7 ± 7.0 mg, respectively whereas their dry masses were 47.7 ± 4.8 to 63.7 ± 5.4, 176.7 ± 6.7 to 204.7 ± 5.6 and 62.8 ± 3.0 to 78.7 ± 2.1 mg, respectively. The length of wing and tibae were observed 8.14 ± 0.82 to 8.47 ± 0.73 and 4.30 ± 0.51 to 4.47 ± 0.32 mm, respectively. The L0:D24 photoperiodic condition produced heavier larvae, pupae and adult workers with larger wings and tibiae and worker’s body size and mass decreased significantly when the bees were reared under L16:D8 and L24:D0 conditions. Key words: Bumblebee; Body mass and size; Photoperiod DOI: http://dx.doi.org/10.3329/bjsir.v46i4.9589 BJSIR 2011; 46(4): 447-450